Problems of criminal legal characterization of crimes related to illegal transplantation committed by transnational organizations under Ukrainian criminal law - Zherzh, Liudmyla Anatoliivna (Norwegian Journal of development of the International Science, 2020)
In the article, the author analyses the main problems encountered in determining the criminal legal characteristics of crimes related to illegal transplantation committed by transnational organizations under Ukrainian criminal law. The Ukrainian judicial statistics on criminal proceedings involving transnational organizations performing illegal transplants are considered. Based on the results of the study, the author proposes concrete proposals to improve the national criminal legislation of Ukraine in order to overcome the problems considered, which arise in practice when characterizing crimes related to illegal transplantation committed by transnational organizations.

У статті аналізуються основні проблеми, які виникають при визначенні кримінально-правової характеристики злочинів, пов’язаних із незаконною трансплантацією, вчинених транснаціональними організаціями за кримінальним законодавством України. Розглянуто українську судову статистику по кримінальним провадженням за участю транснаціональних організацій, що вчиняють незаконні трансплантації. За результатами проведеного дослідження автором запропоновано конкретні пропозиції по вдосконаленню національного кримінального законодавства України з метою подолання розглянутих проблем, які виникають на практиці при кваліфікації злочинів, пов’язаних із незаконною трансплантацією, вчинених транснаціональними організаціями.
Keywords: transplantation; human anatomical materials; transnational organization; transnational organized crime; a transnational organized criminal group; трансплантація; анатомічні матеріали людини; транснаціональна організація; транснаціональна організована злочинність; транснаціональне організоване злочинне угруповання